A POLITIZAÇÃO “EXPLOSIVA” DO GÁS DE XISTO: contribuições críticas para o estudo do Fracking - Benilson Borinelli (Universidade Federal do Maranhão, 2020)
The controversial fracking method for shale gas extraction and its socio-environmental impacts has brought to light disputes over political decisions and capitalist state. Given the theme's relevance and the incipient number of studies in Brazil, this article analyzes how decisions about fracking have been approached from functionalist and critical perspectives. We developed a bibliographic and descriptive research, supported mainly by international literature. While both perspectives make important contributions, critiques' ones can best capture the power relations at stake in decisions about fracking and foster engagement against new injustices. Further studies will be needed in Brazil due to the theme complexity, the continuity of pro-fracking projects and the current intensification of neoliberal deregulation of environmental policies.